Peran Packaging Terhadap Tingkat Nilai Jual Produk Olahan Keripik Buah - Lena Ahdiani Hayati (CV. Publikasi Indonesia, 2021)
Along with the times, market competition is increasing. Not only in conventional world transactions, now people are turning to the digital world. With the increasingly sharp competition situation, aesthetics is an added value that can serve as a medium to attract consumers. The challenge for the fruit chip business world is how the product can have a high brand value in the market area. In accordance with the purpose of this study is to know how the role and function of packaging that menark to the impact and selling value of processed products fruit chips on the market. This research is a research with descriptive qualitative approach with the type of case study (case study. Based on the research results, fruit chips processed products experience various marketing problems due to a lack of innovation in packaging product, so they do not have an attractive power for consumers. Therefore packaging is a powerful strategy in marketing and market strategies, this is done as an effort to develop fruit chips processed products.